2020
DOI: 10.3390/biom10010104
|View full text |Cite
|
Sign up to set email alerts
|

IL10 rs1800872 Is Associated with Non-Steroidal Anti-Inflammatory Drugs Exacerbated Respiratory Disease in Mexican-Mestizo Patients

Abstract: Non-steroidal anti-inflammatory drugs (NSAID) exacerbated respiratory disease (N-ERD) is a disease integrated by asthma, nasal polyps, and hypersensitivity to non-steroidal anti-inflammatory drugs (NSAID). Genetic association studies have explored single nucleotide polymorphisms (SNPs) in genes involved in theoretical pathophysiological mechanisms, but most of these lack replication of findings in second populations. Our objective was to evaluate the association of SNPs in candidate genomic regions described i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
2
0
1
Order By: Relevance
“…Although it has been reported that some genes involved in inflammation are associated with respiratory diseases [ 87 , 88 , 89 , 90 , 91 , 92 ], investigations regarding genetic factors involved in the susceptibility and severity are scanty. Two primary examples in inflammatory response genes, where genetic variability is associated with an altered phenotype, are TNF-α and IL-1β; both are pleiotropic modulators critical in regulating inflammation.…”
Section: Genetic Variants and Influenza A H1n1 Virus Infectionmentioning
confidence: 99%
“…Although it has been reported that some genes involved in inflammation are associated with respiratory diseases [ 87 , 88 , 89 , 90 , 91 , 92 ], investigations regarding genetic factors involved in the susceptibility and severity are scanty. Two primary examples in inflammatory response genes, where genetic variability is associated with an altered phenotype, are TNF-α and IL-1β; both are pleiotropic modulators critical in regulating inflammation.…”
Section: Genetic Variants and Influenza A H1n1 Virus Infectionmentioning
confidence: 99%
“…20 However, genetic studies that evaluated approximately 100 patients with N-ERD demonstrated that the LFT and frequency of severe asthma were similar to those of asthma patients. [21][22][23] In our study, we enrolled patients who met the three clinical criteria needed for N-ERD diagnosis and not just those with asthma who were hypersensitive to NSAIDs. The N-ERD patients had similar clinical characteristics to those reported in other published series.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic associations are likely to predispose to N‐ERD as well as to asthma, chronic rhinosinusitis, and allergic rhinitis 17 . Exploring the genotypes of the Finnish patients with N‐ERD and a positive family history may reveal more genetic risk factors than those that have been suggested as predisposing to N‐ERD 18,19 . This could offer new insights into the pathogenesis of the condition, as well as help develop novel therapeutic options.…”
Section: Discussionmentioning
confidence: 99%